A self-divided poet : form and texture in the verse of Thomas Hood - Edgecombe, Rodney Stenning (Cambridge Scholars, 2006)
Whereas Thomas Hood has long been regarded as a minor comic poet, this book--the first to devote itself exclusively to his verse--provides a detailed analysis of two ""serious"" poems (""Hero and Leander"" and ""The Plea of the Midsummer Fairies"") so as to give a better sense of his range. Most commentators have pointed to the influence of Keats on such occasions, but close examination reveals an even greater debt to Elizabethan and Metaphysical poets, whose sometimes playful deployment of the conceit struck a chord in his sensibility. At the same time, the book gives Hood's comic genius its.